Identifikasi Potensi Resiko dan Bahaya Kerja pada Proses Produksi Garden Stakes di CV. Zara Pangestu - Adithia, Totti; Nurwidiana, Nurwidiana (UNIVERSITAS SERAMBI MEKKAH, 2025)
Zara Pangestu is a company operating in the wood industry. The product produced is Garden Stake or can also be called a plant support. Zara Pangestu is also included in the company with a high risk of work accidents. The aim of this research is to identify the potential risk of work accidents in the production process at CV. Zara Pangestu and provided recommendations for implementing Occupational Health and Safety. The method used in this research is JSA. The results of this research are that the risk category of potential dangers in the Garden Stakes production process has 2 potentials in the low category, 6 potentials in the medium category, and 7 potentials in the high category. The recommendation given to the Company is that the Company should pay attention to Occupational Safety and Health in every Garden Stakes production process from the first station to the final station. Procurement of PPE that complies with standards must also be considered so that every worker who will work feels safe and comfortable and minimizes the rate of work accidents that could occur at any time. The provision of Light Fire Extinguisher must also be considered at each work station to minimize the occurrence of undesirable things such as short circuits which can cause fires and potentially cause losses to the Company. From several K3 implementations that are not optimal, it is hoped that there will be efforts to increase the implementation of K3 in the Company, requiring regular evaluations to always increase the importance of working in a healthy and safe condition.